Sitting patterns after relocation to activity-based offices: A controlled study of a natural intervention - Hallman, D.; Mathiassen, Svend; Jahncke, H. (Elsevier BV, 2018)
© 2017 The Authors This study determined the effect of relocating workers from traditional to activity-based offices on objectively measured sitting patterns. Office workers (n = 493) from five office-sites within a large Swedish government agency were included in a controlled study of a natural intervention (2015–2017). At four sites, traditional offices were replaced by activity-based offices, while workers at one site with no relocation acted as controls. Sitting, standing and walking were measured objectively for 5–8 days in a sub-sample (n = 110) using accelerometry (Actigraph). Total sitting time (% of working time) and time spent in short (< 5 min), moderate (5–30 min) and prolonged (> 30 min) uninterrupted periods in sitting were determined. Intervention effects were determined at 3- and 12-month follow-ups using linear mixed models adjusted for baseline age, gender and office type, and stratified by office-site (referencing controls). The relocation to activity-based offices did not result in an overall effect (across sites) on occupational sitting time (all p > 0.05), while walking time had increased significantly by 1.4% of the working time at 12 months compared with controls. Heterogeneous results were found across offices after 12 months on total sitting time compared with controls (estimated change - 18.3% time–1.4% time), prolonged sitting (change - 18.3% to - 3.8%), walking (change 0.5%–3.5%) and standing (change - 1.4%–13.9%). In conclusion, relocation to activity-based offices had a limited overall effect on occupational sitting patterns in the studied organization, but differed considerably between office sites. Site-specific determinants of sitting behavior in activity-based offices need be identified.